The implementation of SDG12 in and from higher education institutions: universities as laboratories for generating sustainable cities - Martínez-Acosta, Mariajulia; Vázquez-Villegas, Patricia; Mejía-Manzano, Luis Alberto; Soto-Inzunza, Gladis Valeria; Ruiz-Aguilar, Karina Mayela; Kuhn Cuellar, Luis; Caratozzolo, Patricia; Membrillo-Hernández, Jorge (Frontiers in Sustainable Cities, 2023)
It is known that the world is facing and will face significant sustainability challenges. Sustainable Development Goal 12 (SDG12), responsible consumption and production, is one of the most relevant SDGs for building Sustainable Cities. This study is based on the analysis of the implementation of SDG12 in cities, starting from universities as laboratories or first examples of sustainability. The study was carried out through a multilevel scale approach. A systematic review of the literature (global scale) of the last five years (2018-2022) was conducted. It indicated that the main themes or aspects addressed in SDG12 by higher education institutions were sustainable food, supply chains, community, infrastructure, technology, policies, energy consumption, the collaborative economy, smart cities, and curricula. An analysis of the program and the initiatives of a Higher Education Institution (Tecnologico de Monterrey) is presented (local scale), highlighting the Distrito Tec project, 37 institutional initiatives, and 26 courses directly related to SDG12. A survey applied at this University (micro-scale) showed that 8% considered SDG12 the most important of the SDGs and stated that this goal is necessary to reduce environmental impacts. As the most significant impact that Universities can have on SDG12, 52% of the population considers that Universities should become living labs in the transition towards sustainable cities, followed by 36% who think it would be better to implement operational facilities. In comparison, 28% mentioned that the impact could be through research on this production and responsible consumption. In summary, the study indicates that SDG 12 has been achieved by universities in different ways, which overlaps widely with the performance of other SDGs.